Assessing the Correlation between Spicy Food Consumption and Dyspepsia Symptoms in Medical and Health Students at Atma Jaya Catholic University of Indonesia - Lonah; Divara Ariesta Sekar Suryadi, Made; Arieselia, Zita; Vitria Kurniawan, Sandy; Hananta, Linawati; Setiawan, Jonny; Surjono, Edward; Santosa, Mariani; Ulina Margareta Situmorang, Evi; Fan, Tan Fei; Yuliana; Budiyanti, Ecie (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2024)
Introduction: The capsaicin (8-methyl-N-vanillyl-6-nonenamide) content in spicy foods can trigger irritation and increase gastric acid production, which potentially damages the stomach mucous layer by increasing chloric acid levels (HCl). It is known that dyspepsia has a variety of causes and one of them can be triggered by the consumption of irritating foods, such as spicy foods. Therefore, the research was conducted to determine whether there was a significant relationship between the consumption of spicy foods and the incidence of dyspepsia in students of the Faculty of Medicine and Health Sciences at the Atma Jaya Catholic University of Indonesia. Methods: This research method is an analytical observational study using cross-sectional methods. The main variables in this study were dyspepsia, measured using the Rome III questionnaire, and the frequency of spicy food consumption measured using the Food Frequency Questionnaire (FFQ). The sample consisted of 107 people randomly selected. The data was analyzed statistically using the Fischer Exact test. Results: This study showed that 56.1% of respondents frequently eat spicy foods, while the majority, as much as 95.3%, also have dyspepsia. There was a significant correlation between spicy eating habits and dyspepsia, with a p-value of 0.014 (p<0.05). Conclusion: The results showed a statistically significant relationship between spicy eating habits and dyspepsia, so it is recommended for students to reduce spicy food consumption as it can affect the onset of dyspepsia. Keywords: dyspepsia - spicy foods - stomach - Rome III questionnaire - food frequency questionnaire